2018
DOI: 10.1371/journal.pone.0209902
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance characteristics of Mycobacterium tuberculosis isolates between 2014 and 2017 in Sichuan, China: A retrospective study

Abstract: BackgroundThe prevalence of drug-resistant tuberculosis (DR-TB) has brought severe challenges to the prevention and control of tuberculosis. Studies have explored the status of antituberculosis drug (ATD) resistance in different regions of China. However, few studies have focused on DR-TB in Sichuan to date. Due to the large population in Sichuan, detailed investigations of the DR-TB burden in Sichuan are needed. The objective of this study was to investigate the drug resistance characteristics of TB isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
5
21
1
Order By: Relevance
“…The Fifth National TB Epidemiological Survey of China shows that NTM accounted for 11.1% in isolated mycobacteria strain, M. bovis 2.5%. [12] In this study, the proportion of the 2 are both higher than the national average level, and the drug resistance rates are higher, especially the drug resistance rate of NTM increased to 100%, consistent with the report of Zhou et al [13] The drug susceptibility of NTM depends on mycobacterial type. Slow-growing NTM usually are susceptible to first-line anti-TB drugs.…”
Section: Discussionsupporting
confidence: 90%
“…The Fifth National TB Epidemiological Survey of China shows that NTM accounted for 11.1% in isolated mycobacteria strain, M. bovis 2.5%. [12] In this study, the proportion of the 2 are both higher than the national average level, and the drug resistance rates are higher, especially the drug resistance rate of NTM increased to 100%, consistent with the report of Zhou et al [13] The drug susceptibility of NTM depends on mycobacterial type. Slow-growing NTM usually are susceptible to first-line anti-TB drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, no microscopic lesions were observed in the small intestine in the B. subtilis strain WS-1 treatment group after E. coli infection (Figure 7), which furthered our understandings of the role of the B. subtilis as a probiotic. It was reported that several lipopeptides such surfactin, secreted by B. subtilis , can confer strong antipathogenic effects and thus benefit the host by balancing the intestinal microbiome (Zhou et al, 2018). Polyketide from the seaweed-associated heterotrophic bacterium B. subtilis MTCC 10403 has potential antibacterial activities against clinically important pathogens (Chakraborty et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The critical concentration of Mycobacterium tuberculosis drug sensitivity test is based on CLSI M24-A2 and FDA-approved standards for drug susceptibility testing. Among them, the critical concentration of cycloserine is derived from the FDA-approved standards (https://www.accessdata.fda.gov/spl/data/a0f29de7-d7cd-45a0-915a-eae2562edaf8/a0f29de7-d7cd-45a0-915a-eae2562edaf8.xml), and the rest are from CLSI M24-A2 (Woods et al, 2011; Zhou et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In China, there were an estimated 7.1% of initial treated TB cases with MDR/RR-TB and an estimated 14% of re-treated TB cases with MDR/RR-TB (World Health Organization, 2018). The prevalence of MDR-TB varied from region to region, 14.3% in Guizhou (Lan et al, 2019), 8.0% in Hangzhou (Li et al, 2018), 13.3% in Sichuan (Zhou et al, 2018), 13.2% in Hebei (Li et al, 2016), 9% in Beijing (Liu et al, 2018), and 5% in Shanghai (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%